Report of the consultative workshop on the structure and functioning of the African opportunity crops working group for the African seed and biotechnology programme - Grazioli, Francesca; Otieno, Gloria; Mendonce, Sharon; Acasto, Filippo; El Bilali, Hamid (2025)
This report highlights the outcomes of a high-level consultative workshop convened under the EU-funded SUSTLIVES project, which promotes the strategic use of neglected and underutilized species (NUS)—now repositioned as “Opportunity Crops”—to enhance food and nutrition security, support resilient livelihoods, and contribute to climate adaptation in Burkina Faso and Niger.